Potential of Bayan Indigenous Peoples in Obtaining Customary Forest Management Rights in North Lombok Regency - B, Kornelia Webliana; Jemarut, Wihelmus; Ichsan, Andi Chairil; Sukma Rini, Dwi; Valentino, Niechi; Anwar, Hairil; Permatasari, Diah; Andrie Ridzki Prasetyo (Jurnal Multidisiplin Madani, 2024)
In Bayan Village, West Nusa Tenggara, there are four customary forest areas that have the potential to be developed through the Customary Forest scheme. This scheme is part of the Social Forestry Program which provides access and forest management rights to indigenous communities. The four forests are currently being managed by the indigenous peoples but have not yet been granted the status of customary forest. The aim of this study is to evaluate the potential of the Bayan indigenous community to acquire forest management rights under the Customary Forest scheme. The research employed a normative-empirical approach. The results indicate that the Bayan indigenous peoples meets all the criteria in the Government Regulation No. 23 of 2021 on the Implementation of Forestry and the Ministry of Environment and Forestry Regulation No. 9 of 2021 on Social Forestry Management. The Bayan indigenous peoples is eligible to be designated as a Customary Law Community by the Regent of North Lombok and to obtain Customary Forest management rights from the Ministry of Environment and Forestry. This potential is supported by two factors: (1) the potential for forest and tourism development; and (2) the potential for well-maintained local wisdom.